Synthesis, structural and photophysical properties of mixed Zn:SnO2 nanowires. (1st March 2021) - Mohamed, S.H.; Khan, Mohd Taukeer; Almohammedi, Abdullah; Awad, M.A.
Abstract: The present work demonstrates the structural and photophysical properties of mixed zinc tin oxide (Zn:SnO2 ) nanowires (NWs) synthesized via vapor transport technique with Zn content of 10, 25 and 50 wt%. The XRD spectra reveals the tetragonal phase of SnO2 for 10 wt% Zn content, whereas a combination of tetragonal SnO2 and hexagonal ZnO phases were observed for higher Zn ratios. The SEM images reveals the formation of smooth NWs for low Zn content, whereas a combination of NWs along with spherical nanoparticles have been observed for 50 wt% Zn:SnO2 sample. The optical band gap was decreased from 3.21 eV (10% Zn:SnO2 ) to 2.84 eV (50% Zn:SnO2 ), whereas the corresponding Urbach energy increased from 971 meV to 1132 meV. The refractive index values increased from 2.28 to 2.64 when Zn content increased from 10 to 50 wt%. The absorption spectra showed a red shift and the appearance of new band with increasing Zn wt.%, signaling the formation of new electronic states below the conduction band. The fabricated films displayed a broad steady state emission with peak around 462 nm, which intensity decreased with the increasing of Zn ratio. The effective life time of charge carrier was decreased from 198 ps for 10 wt% Zn:SnO2 to 172 ps for 50 wt% Zn:SnO2 .